SARS-COV-2 INFECTION DURING PREGNANCY AND RISK OF PREECLAMPSIA: A SYSTEMATIC REVIEW - Tua Sihotang, Martin Gabe (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: The concurrence of pregnancy-related diseases (gestational hypertension, preeclampsia and eclampsia) with the COVID-19 virus is a clinical novelty, classified as a serious maternal risk. 1 2 A living systematic review with meta-analysis in pregnant and recently pregnant women reported severe COVID-19 infection in 9 the intensive care unit admission required in 4%; invasive ventilation used in 2 and extracorporeal membrane oxygenation administered in 0.2The aim: This study aims to show about SARS-CoV-2 infection during pregnancy and risk of preeclampsia. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 99 articles, whereas the results of our search on SagePub brought up 66 articles. The results of the search conducted for the last year of 2013 yielded a total 98 articles for PubMed and 36 articles for SagePub. The result from title screening, a total 2 articles for PubMed and 16 articles for SagePub. In the end, we compiled a total of 8 papers. We included five research that met the criteria. Conclusion: The characteristics of SARS-CoV-2-infected pregnant women and preeclamptic women seem to be more or less similar with regard to proteinuria, elevated liver enzymes, thrombocytopenia, and increased pro-inflammatory markers. Hence, diagnosis of preeclampsia could be quite difficult.